The Bioarchaeology of Social Control Assessing Conflict and Cooperation in Pre-Contact Puebloan Society - Harrod, Ryan P. (Bioarchaeology and Social Theory, 2017)
XIX, 172 p. 13 illus., 5 illus. in color.